Serum Acetylcholinestrase (Ache) Activity At Different Stages Of Gestation In Triple Cross Cattle - Padodara, R. J.; Arya , J. S. (Indian Journal of Veterinary Sciences and Biotechnology, 2012)
Serum Acetylcholinestrase (AChE) activity (mmol/ml/hr) was studied in triple cross pregnant heifers (20) and cows (24) at days 90, 150, 210 and 275 of gestation. AChE activity significantly (P
Keywords: Acetylcholinestrase; Gestation; Triple Cross Cattle